Promising properties and future trend of eutectic high entropy alloys - Lu, Yiping; Dong, Yong; Jiang, Hui; Wang, Zhijun; Cao, Zhiqiang; Guo, Sheng; Wang, Tongmin; Li, Tingju; Liaw, Peter K. (Scripta materialia, 2020)
Eutectic high-entropy alloys (EHEAs), as a sub-group of high-entropy alloys (HEAs), are becoming a new research hotspot in the metallic materials community because of their excellent castability, fine and uniform microstructures even in the as-cast state, high strength, and good ductility. Some of the EHEAs have shown promising potentials for industrial applications. Here, the history, interesting solidification microstructure and mechanical properties, and the design strategy of EHEAs are reviewed, and their future prospects are outlined. [Display omitted]